Peculiarities of Modifications in Geometric Parameters and Changes in Osmotic Fragility of Human Erythrocytes Following Their Exposure in Sucrose and PEG-1500 Solutions - Zemlianskykh, Nina G.; Kovalenko, Igor F.; Babijchuk, Lyubov A. (Problems of Cryobiology and Cryomedicine, 2017)
The effect of be polyethylene glycol with a molecular weight of 1500 (PEG-1500) and sucrose on the changes in geometric parameters and osmotic fragility of human erythrocytes was studied. At equal mass fractions of two substances, sucrose caused more pronounced changes in the distribution of erythrocytes according to direct light scattering (FSC) in comparison with PEG. Nevertheless, PEG induced a shift in the distribution of erythrocytes according to the sphericity index in the direction of the spherical cell types, and also increased the osmotic fragility of the erythrocytes relative to the intact and incubated in the presence of sucrose cells. Stomatocytosis was the prevailing trend of the shape modification in the PEG presence, while the effect of sucrose led to the dominance of dehydrated flattened cells. Differences in the external manifestations of the erythrocyte response to PEG and sucrose solutions, accompanied by unequal changes in osmotic fragility, indicate the role of structural membrane modifications induced by cryoprotectants for cell stabilization during subsequent freezing. Probl Cryobiol Cryomed 2017; 27(4): 296–310